2017
DOI: 10.1136/bmjgh-2017-000333
|View full text |Cite
|
Sign up to set email alerts
|

Use of standardised patients to assess quality of healthcare in Nairobi, Kenya: a pilot, cross-sectional study with international comparisons

Abstract: IntroductionThe quality of clinical care can be reliably measured in multiple settings using standardised patients (SPs), but this methodology has not been extensively used in Sub-Saharan Africa. This study validates the use of SPs for a variety of tracer conditions in Nairobi, Kenya, and provides new results on the quality of care in sampled primary care clinics.MethodsWe deployed 14 SPs in private and public clinics presenting either asthma, child diarrhoea, tuberculosis or unstable angina. Case management g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
95
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(101 citation statements)
references
References 32 publications
5
95
1
Order By: Relevance
“…Moreover, referral links to the National Tuberculosis Programme are weak, with data from standardised patient studies in these three countries showing that only 28% to 45% of patients were correctly managed by primary care providers. 34,35,46 Simply put, the global capacity to diagnose, link to care, treat, and cure patients with tuberculosis is woefully inadequate for the massive burden of disease that exists. The public health implications, as well as the poor clinical and financial implications for patients, 41 are self-evident.…”
Section: Insufficient Investment and Political Willmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, referral links to the National Tuberculosis Programme are weak, with data from standardised patient studies in these three countries showing that only 28% to 45% of patients were correctly managed by primary care providers. 34,35,46 Simply put, the global capacity to diagnose, link to care, treat, and cure patients with tuberculosis is woefully inadequate for the massive burden of disease that exists. The public health implications, as well as the poor clinical and financial implications for patients, 41 are self-evident.…”
Section: Insufficient Investment and Political Willmentioning
confidence: 99%
“…Unfortunately, cascade of care analyses shows large gaps in the quality of care for both adults and children, and for both drug-susceptible and drug-resistant tuberculosis in many high-burden countries. [36][37][38]112,133 Standardised patient studies in India, Kenya, South Africa, and China [33][34][35]46 have shown that the quality of care for tuberculosis is poor. In a study in China, for example, health-care providers did not correctly manage patients presenting with archetypal symptoms or results suggesting active tuberculosis 59% of the time.…”
Section: Improving Quality Management To Ensure High-quality Service mentioning
confidence: 99%
See 1 more Smart Citation
“…We excluded 12 articles: two because the data applicable to the review was already included in the authors' other included publication, [15,16] two because data were not original to research manuscripts (one commentary and one systematic review), [7,17] seven studies because they did not report data that could be mapped to our pre-defined patient categories, and one because it was a community-based study. [18][19][20][21][22][23][24] Description Of Studies The 14 eligible studies were published between 2000 and 2018 and reported data from India, [25][26][27][28][29] South Africa, [9,[30][31][32] Kenya, [33] Thailand, [34] China, [35] Vietnam [36] and Ghana [37] (Table 1).…”
Section: Selection Of Studiesmentioning
confidence: 99%
“…They have shown that the quality of primary care in low-and-middle-income countries was poor. [11][12][13][14][15][16] Most cases were incorrectly diagnosed based on a very lenient definition, and simple medical conditions were improperly managed in the majority of cases. Antibiotics were usually inappropriately overprescribed, and it was less likely for primary care providers to refer patients to higher-level hospitals for specialist care when needed.…”
mentioning
confidence: 99%